BIOLOGÍA REPRODUCTIVA DE Ethmidium maculatum “machete” (Valenciennes, 1847) PROVENIENTE DE LA REGIÓN LA LIBERTAD, DE MAYO 2017 A ABRIL 2018. - Nureña Muñoz, Maria Soledad (2018)
The reproductive biology of Ethmidium maculatum "machete" from the La Libertad region of May 2018 was studied. The sample consisted of 471 specimens obtained from artisanal fisheries in the ports of Pacasmayo, Puerto Morín and Salaverry. The gonadosomatic index, reproductive activity, spawning frequency, as well as fecundity were determined and a gonadal maturity scale was elaborated. Through the infiltration method, sex cells are seen microscopically in males and females. The highest spawning peaks are shown in the months of March and April (autumn) in both sexes. Reproductive activity and frequency of desire are presented with higher values in the summer and autumn seasons. For fecundity, the parameter that was best adjusted was the body weight of the fish with r = 0.57. Different types of sex cells were observed along the gonadota, in females five types of cells were determined: immature, pre-vitelogenated, vitelogenated, mature and hydrated while in males three spermatographic types, spermatocytes and sperm. The gonadal maturity scale was determined macroscopically and microscopically validated, five phases were established for both sexes, the recovery phase (V) for females and virgin (0) for males and the absent ones. Concluding that the "machete" is a partial spawner, presenting a mayor spawning in autumn.